Contribution of anthropogenic vibration sources to crack growth in natural rock arches - Finnegan, Riley; Moore, Jeffrey R.; Geimer, Paul R. (Frontiers in Earth Science, 2022)
Natural arches are culturally valued rock landforms common in sedimentary rocks of the Colorado Plateau and additionally occur broadly around the world. Recent notable collapses of some of these landforms have highlighted the need to better understand the mechanics of their failure. While environmentally driven weathering has been the focus of most previous studies of arch collapse, comparably little attention has been given to anthropogenic vibration sources and how these often slight- to moderate-magnitude shaking events might steadily weaken arches over time. We collected 12–15 months of continuous ambient vibration data from arches and nearby bedrock in both anthropogenically ‘noisy’ and ‘quiet’ locations and used these datasets to develop an annual model of arch peak ground velocity based on magnitude-cumulative frequency distributions. Working from these models, we added vibration events of varying magnitude or frequency of occurrence, informed by field data, imitating arch vibration in response to different anthropogenic activities such as helicopter flights or induced earthquakes. We then applied subcritical fracture mechanics principles to predict annual crack growth rates in an idealized arch under these different vibration conditions. Our results demonstrate that in a single year, cracks grow minimally longer (∼1%) in ‘noisy’ environments than in areas not experiencing anthropogenic vibration energy. Few (1+) 30-s moderate-magnitude events (∼15 mm/s) or many (>37,000) 30-s low-magnitude events (∼2 mm/s) cause markedly increased crack growth. Our approach provides a valuable new framework for assessing the range and frequency of occurrence of vibrations experienced by an arch, and for predicting arch damage. Our results, in turn, yield important new outputs applicable in support of conservation management of these and similar landforms world-wide under exposure to a range of human-induced vibration activity.